Optimizing DNA extraction condition from wood using response surface methods - Thinh, Du Phuc; Kim Hong, Tang Thi; Biet, Huynh Van (Vietnam Journal of Science and Technology, 2017)
The DNA extraction is one of the first steps and plays animportant role in study on genome of any species on earth. Depending on the purpose and object of study, DNA can be extracted from various tissues.For plants, DNA is usually extracted from the leaves, seeds and young buds, in which these tissues are the best DNA source and can be extracted easily. However, the collection of sample from mature trees, which are generally tall, isdifficult and need more facilities. Consequently, it leads to be limited for the study scope.The proposed solutionis to use a wood tissue instead ofthe leaves, seeds and young due to they are easily collected. The problem is very difficult to extract high quality DNA from the wood tissue (Verbylaite et al., 2010). However, if the extraction of DNA from wood tissue would besuccessful, it would open up many research directions and could turn techniques that seemed unfeasible before into the effective solution. Extracting and analyzing DNA from dried wood and processed wood could be developed to explore the possibility of identifying the species and theirorigin. This could be greatly useful for determining the legality of wood log and wood products, and for deterring trade in illegal wood products (Tsumura et al.,2011). Currently, there are some commercialized kits, enabling DNA extraction from wood more easily,e.g. DNeasy Plant Mini Kit (Qiagen), Nucleospin Plant II (Macherey-Nagel), Genomic DNA Purification Kit (Fermentas) and innuPREP Plant DNA Kit (Analytik Jena). However, the commercial Kitsare expensive.  Meanwhile, there are some cheaper methods, applying for DNA extraction from wood successfully, such as SDS method (Edwards et al.,1991; Goodwin and Lee, 1993), protein precipitation protocol (Dellaporta et al., 1983; Fang et al., 1992), especially CTAB method, obtaining with a high DNA concentration (Doyle J and Doyle H., 1987). The DNA extracted by CTAB protocol is less pure; however, they are still suitable to use in molecular biology. The objective of this work was to optimize the conditions of CTAB protocol for DNA extraction from wood. The two parameters centrifugation time and volume ratio of isopropanol to solutions containing DNA that affect the yield and quality DNA were explored using the response surface methodology (RSM). The central composite design (CCD) was used to obtain the experimental design matrix. This approach has limited number of actual experiments performed where as allowing probing into possible interaction between these parameters studied and their effect on quantity and quality DNA.